Antifungal potential of silver and copper nanoparticles against Lasiodiplodia theobromae causing stem-end rot of mango - Vu Mai Linh, Nguyen; Hong Thao, Phan Thi; Hong Lien, Nguyen Thi; Hong Van, Dao Thi; Van Hieu, Nguyen; Tuong Van, Nguyen; Hoai Chau, Nguyen (Vietnam Journal of Biotechnology, 2021)
Fungal species Lasiodiplodia theobromae of family Botryosphaeriaceae is a pathogen causing significant loss of production and quality of mango crop in Vietnam and worldwide. In this study, a fungal strain designed as XB1 was isolated from stem-end rot mango fruits, identified and tested its susceptibility to silver and copper nanoparticles. Strain identification based on biological characteristics and sequence analysis of 5.8S RNA indicated that the isolate XB1 was highly close (99%) to Lasiodiplodia theobromae, therefore named as Lasiodiplodia theobromae XB1. The inhibiting effects of Ag and Cu nanoparticles on the growth of L. theobromae XB1 were investigated at various concentrations. After seven days of plate cultivation, nano-Cu at 2000 ppm and 4000 ppm inhibited the fungal growth by 17.9 % and 52.4 %, respectively. With silver nanoparticles of about 20 nm in size, the effect seemed rather limited. At 400 ppm, the highest inhibition of 80% was observed after 4 days, then the growth fully resumed. However, another preparation, i.e. nano silver AgH of about 7 nm in size, showed significantly stronger inhibition against the fungus. At 20 ppm, AgH inhibited 90% of growth, comparable to 400 ppm of either carbendazim or hexaconazole. At 25 ppm, no growth was observed. The results suggested high potential of copper and silver nanoparticles AgH to replace toxic chemicals in controlling fungal pathogens of mango and other fruits.